A preliminary study on the effectiveness of maternal to neonatal transfer of antibodies against SARS-CoV-2 in the women vaccinated with heterologous CoronaVac-ChAdOx1 - Saipin Pongsatha; Theera Tongsong; Jiraprapa Wipasa; Supachai Sakkhachornphop; Sayamon Hongjaisee; Kriangkrai Chawansuntati (Taylor & Francis Group, 2023)
The objective is to evaluate the effectiveness of placental transfer of maternally derived SARS-CoV-2 IgG antibodies after the vaccination of pregnant women with heterologous CoronaVac-ChAdOx1. Thirty pregnant women were vaccinated with CoronaVac as the first dose, followed by ChAdOx1 3 weeks later. The antibody levels in the maternal blood and in the umbilical cord blood at the time of delivery were determined. The results showed that the vaccination effectively increased antibody levels in both mothers and newborns. The antibody levels in the mothers were strongly correlated with those in the newborns (P < .001). The high levels of passive immunity in the newborns were achieved when the first and second doses of vaccination were given more than 40 and 20 d before delivery, respectively. After 1 month of the second dose, the immune levels seemed to decline in the mothers but increase in the newborns. The antibody levels in the newborns appear to be higher than those in the mothers in cases of delivery after 20 d of the second dose (1419 ± 699 vs 1222 ± 593 BAU/L; p < .05). In conclusion, heterologous CoronaVac-ChAdOx1-S schedule can increase antibody levels in a short time during pregnancy. Also, the regimen effectively increases immunity in the newborns. The antibody levels in the newborns appear to be higher than that in the mothers in most cases, if receiving the second dose more than 3 weeks before delivery. Therefore, the regimen should be considered as an effective regimen for pregnant women, especially in settings where mRNA vaccine is not available.